Hypoglycaemic Potential of Methanol Stem-Bark Extract of Mangifera Indica in Alloxan Induced Diabetic Albino Rats and Its Toxicity Effect to Liver and Kidney - Umaru, Isaac John; Ekubnse, Nkiri Annasthesia; Umaru, Kerenhappuch Isaac; Tansaba, Akafa Andes; Ugoeze, Egeonu Stephen; Nanmar, Chakfa (Darul Yasin Al Sys, 2024)
Mangifera indica (MI), popularly known as mango belong to the genus Mangifera and family Anacardiacea. The leaves, stem bark and roots are used as herbal medicines worldwide. Mango possesses anti-diabetic, anti-bacterial, anti- oxidant, anti-viral and anti-inflammatory properties. This research focuses on the hyperglycemic and antibacterial capacity of methanol stem bark extract of Mango tree in alloxan induced diabetic albino rats to combat its fatal consequences in humans. This work is carried out to determine the hypoglycemic capacity of methanol stem bark extract of Mangifera indica in alloxan-induced diabetic albino rats at different volumes (ml) of administration, to also determine the antibacterial capacity of methanol stem bark extract of Mangifera indica in alloxan-induced diabetic albino rats at different volumes (ml) of administration and to test the efficacy of methanol stem bark extract of Mangifera indica in alloxan-induced diabetic albino rats. Fresh stem bark (trunk) of Mangifera indica were collected in the Federal University Wukari school premises, were air dried for 21 days, pounded into powder, cold macerated in methanol, filtered and extract was gotten. 27 diseased-free (healthy) albino rats which were purchased at Yola, Adamawa State, were kept in different cages to enable proper analysis at the cause of the work. Results of liver function indices showed that treatments with 100 mg/kg, 200mg/kg and 400mg/kg body weight of Mangifera indica stem bark methanolic extract were able to restore liver function parameters at different levels of concentrations. Treatments with standard drug and all the doses of the extract were able to counteract the elevated effect of alloxan in some kidney parameters such as serum urea level at 200mg/kg with (25.23±1.98a) and (1.05 ±0.14a) for creatinine at 200mg/kg respectively. The result of this study shows that the stem back extract possessed as an agent for hypoglycaemic. These can serve as possible source of raw material for pharmaceutical products. However, the extract is found not to be harmful to the liver and kidney and should be used as health remedy for certain diseases such as hyperglycaemic and bacterial effects.